Changes in Aquaculture - Subasinghe, Rohana (2021)
Global aquaculture production in 2017 (animals and plants) was recorded as 111.9 million tons, with an estimated first-sale value of $249.6 billion. Since 2000, world aquaculture has ceased to enjoy the high annual growth rates of the 1980s and 1990s (11.3 and 10.0 per cent, respectively). Nevertheless, it continues to grow at a faster rate than other major food production sectors. Annual growth declined to a moderate 5.8 per cent during the period from 2000 to 2016, although double-digit growth still occurred in a small number of countries, in particular in Africa, from 2006 to 2010. Fish produced by this rapidly growing sector is high in protein and contains essential micronutrients, sometimes essential fatty acids, which cannot easily be substituted by other food commodities...